VD_FINDINFO Décision / 2013 / 159 vom 13. August 2012 - VD Tribunal cantonal (2012)
RISQUE DE FUITE, RISQUE DE RÉCIDIVE, DÉTENTION PRÉVENTIVE, PROLONGATION | 187 CP, 190 CP, 221 al. 1 let. a CPP (CH), 221 al. 1 let. c CPP (CH), 221 CPP (CH), 222 CPP (CH), 227 CPP (CH), 237 CPP (CH), 393 al. 1 let. c CPP (CH)